Multigroup Analysis of the Relationships Between Self Efficacy and Academic Anxiety: The Mediating Role of Psychological Flexibility Across Gender in Adolescent Students - Falah Nodehi , Masoumeh; Solgi , Zahra; Torabi , Omid; Rahmani, Samira; Hosseiny, Mina (Iranian Journal of Educational Sociology, 2026)
Purpose: The present study aimed to examine the multigroup model of the relationships between self efficacy and academic anxiety with the mediating role of psychological flexibility based on gender among adolescent students.Materials and Methods: This study was a descriptive–correlational and cross sectional research using structural equation modeling and multi group analysis (MGA). The statistical population consisted of all male and female adolescent students studying in the fields of experimental sciences, mathematics, and humanities in Tehran from November to December 2025. The sample included 121 adolescents (56 boys and 65 girls) who were selected through multistage cluster sampling. The research instruments included the General Self Efficacy Scale (GSE 17), the Psychological Flexibility Questionnaire (PFQ), and the Academic Performance Questionnaire (APQ). Descriptive statistics were analyzed using SPSS version 27, and path analysis and multi group analysis (MGA) were conducted using SmartPLS version 4. The significance level was set at 0.05.Findings: The findings indicated that the path from psychological flexibility to debilitating anxiety was negative and significant among girls (β = −0.455, p < 0.001) but not significant among boys (β = 0.258, p = 0.463). Psychological flexibility was positively and significantly related to facilitating anxiety among girls (β = 0.508, p < 0.001), whereas this relationship was not significant among boys (β = 0.330, p = 0.121). The path from self efficacy to debilitating anxiety was negative and significant among girls (β = −0.562, p < 0.001) and negative but not significant among boys (β = −0.589, p = 0.062). Furthermore, the relationship between self efficacy and facilitating anxiety was positive and significant among boys (β = 0.519, p = 0.016) but not significant among girls (β = 0.220, p = 0.126). The results also showed that the path from self efficacy to psychological flexibility was positive and significant in both groups (girls: β = 0.741, p < 0.001; boys: β = 0.903, p < 0.001), with a significant difference between the two groups (p = 0.012). In addition, the indirect effects of self efficacy on debilitating anxiety (β = −0.337, p < 0.001) and facilitating anxiety (β = 0.376, p < 0.001) through psychological flexibility were significant only among girls and were not significant among boys (p > 0.05).Conclusion: The findings suggest that psychological flexibility plays a significant role in explaining the relationship between self efficacy and academic anxiety among adolescents, and that these relationships differ by gender. These findings highlight the importance of strengthening self efficacy and especially enhancing psychological flexibility as potential strategies for managing academic anxiety among students, particularly girls. Moreover, considering gender differences in designing educational and psychological interventions may help improve adolescents’ mental health and academic functioning.